Houses and Domestic Space in Seventeenth and Eighteenth Century Hospitaller Malta - Said-Zammit, George A., author.
1 online resource
Keywords: Houses and Domestic Space in Seventeenth and Eighteenth Century Hospitaller Malta is a study concerned with a wide spectrum of early modern dwellings in Malta, ranging from palazzi and affluent residences to peasant dwellings, troglodyte houses, and hovels. The multifaceted approach adopted in this book allows houses and domestic networks to be studied not only in terms of architecture and construction materials, but also as places of human habitation where house dwellers act, react and interact in different contexts and circumstances. Dwellings are places that permit different social and economic activities, whilst providing shelter and security to the household members. Through the available sources, the houses of Hospitaller Malta are analysed in terms of their spatial properties and how they generate privacy, interaction and communication, identity, accessibility, security, visibility, movement and encounters, and, equally important, how domestic space relates to gender roles, status, and class. This work, therefore, seeks to reach a deep and nuanced understanding of domestic space and how it relates to the islands' history and the development oftheir society during the seventeenth and eighteenth centuries.